2009
DOI: 10.1038/emboj.2009.155
|View full text |Cite
|
Sign up to set email alerts
|

A PH domain within OCRL bridges clathrin-mediated membrane trafficking to phosphoinositide metabolism

Abstract: OCRL, whose mutations are responsible for Lowe syndrome and Dent disease, and INPP5B are two similar proteins comprising a central inositol 5-phosphatase domain followed by an ASH and a RhoGAP-like domain. Their divergent NH2-terminal portions remain uncharacterized. We show that the NH2-terminal region of OCRL, but not of INPP5B, binds clathrin heavy chain. OCRL, which in contrast to INPP5B visits late stage endocytic clathrin-coated pits, was earlier shown to contain another binding site for clathrin in its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
133
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 60 publications
(87 reference statements)
1
133
0
1
Order By: Relevance
“…OCRL has a broad distribution on endosomes, including PI3P-positive endosomes, and already associates with endocytic vesicles at the internalization step from the plasma membrane (20)(21)(22)35). In contrast, we have shown that APPL1 associates with endosomes at early postinternalization stages (in both clathrin-coated pit-derived vesicles and macropinosomes) and then dissociates as endocytic vesicles become PI3P positive and thus acquire PI3P binding proteins such as WDFY2 and EEA1 (35).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…OCRL has a broad distribution on endosomes, including PI3P-positive endosomes, and already associates with endocytic vesicles at the internalization step from the plasma membrane (20)(21)(22)35). In contrast, we have shown that APPL1 associates with endosomes at early postinternalization stages (in both clathrin-coated pit-derived vesicles and macropinosomes) and then dissociates as endocytic vesicles become PI3P positive and thus acquire PI3P binding proteins such as WDFY2 and EEA1 (35).…”
Section: Resultsmentioning
confidence: 62%
“…OCRL interacts with several endocytic proteins, including clathrin (20)(21)(22)(23), the clathrin adaptor AP2 (21,24), and several endocytic (e. g., Rab5) (25,26) and nonendocytic Rab GTPases (20,26,27). It has a broad distribution on endosomes (24,25) and also is present at late-stage clathrin-coated pits (20,(22)(23)(24) and in the Golgi complex area (23,24,28).…”
mentioning
confidence: 99%
“…It seems unlikely that localized PIP2 production contributes to CCP initiation or maturation because no PIP2-kinases have been localized to CCPs (Sun et al 2007;Antonescu et al 2010). In contrast a variety of PIP 2 (5 0 )-phosphatases (OCRL, Sjn1, and Sjn2) do local-ize to CCPs and play important roles in CCP maturation and budding (Perera et al 2006;Mao et al 2009;Nakatsu et al 2010Nakatsu et al , 2012Taylor et al 2011). A model has therefore emerged in which PIP2 diffusing in the plasma membrane is sequestered at the CCP nucleation site through interaction with a variety of PIP2-binding EAPs and wherein PIP2 turnover plays a key role in CCP maturation and scission (Antonescu et al 2010).…”
Section: Eaps and Endocytic Site Nucleation: Whence The Pits?mentioning
confidence: 99%
“…The Rab5 effector APPL1 (adaptor protein containing pleckstrin homology domain, PTB domain and leucine zipper motif 1) labels a peripheral phosphatidylinositol 3-phosphate (PtdIns3P)-negative endocytic compartment that is a transient station for entry of EGFR into the early endosome (Miaczynska et al, 2004;Zoncu et al, 2009). Linking this compartment to late stages of clathrin-coated pits and newly formed clathrin-coated vesicles is OCRL (oculocerebrorenal syndrome of Lowe), an APPL1-and clathrin-binding inositol 5-phosphatase (Choudhury et al, 2005;Erdmann et al, 2007;Mao et al, 2009). A further OCRL-binding protein, Ses1/2 (also known as IPIP27A/B), associates with the OCRL compartment but because of mutually exclusive binding defines an endocytic sub-population downstream of the APPL1 station (Swan et al, 2010;Noakes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%